Bone mineral density in children with idiopathic nephrotic syndrome - Ghada Mohamed El-Mashad; Mahmoud Ahmed El-Hawy; Sally Mohamed El-Hefnawy; Sanaa Mansour Mohamed (Jornal de Pediatria, 2017)
Objectives: To assess bone mineral density (BMD) in children with idiopathic nephrotic syndrome (NS) and normal glomerular filtration rate (GFR). Methods: Cross-sectional case–control study carried out on 50 children: 25 cases of NS (16 steroid-sensitive [SSNS] and nine steroid-resistant [SRNS] under follow up in the pediatric nephrology unit of Menoufia University Hospital, which is tertiary care center, were compared to 25 healthy controls with matched age and sex. All of the participants were subjected to complete history taking, thorough clinical examination, laboratory investigations (serum creatinine, blood urea nitrogen [BUN], phosphorus [P], total and ionized calcium [Ca], parathyroid hormone [PTH], and alkaline phosphatase [ALP]). Bone mineral density was measured at the lumbar spinal region (L2–L4) in patients group using dual-energy X-ray absorptiometry (DXA). Results: Total and ionized Ca were significantly lower while, serum P, ALP, and PTH were higher in SSNS and SRNS cases than the controls. Osteopenia was documented by DXA scan in 11 patients (44%) and osteoporosis in two patients (8%). Fracture risk was mild in six (24%), moderate in two (8%), and marked in three (12%) of patients. Conclusion: Bone mineralization was negatively affected by steroid treatment in children with NS. Resumo: Objetivos: Avaliar a densidade mineral óssea (DMO) em crianças com síndrome nefrótica idiopática (SNI) e com taxa de filtração glomerular (TFG) normal. Métodos: O estudo transversal de caso-controle foi realizado com 50 crianças: 25 casos de SNI [16 sensíveis a esteroides (SNSE) e nove resistentes a esteroides (SNRE) com acompanhamento na unidade de nefrologia pediátrica do hospital da Menoufia University, centro de cuidados terciário] foram comparados com 25 controles saudáveis do grupo de controle com idade e sexo equivalentes. Todos os participantes foram submetidos a anamnese completa, exame clínico completo, exames laboratoriais [creatinina sérica, nitrogênio ureico no sangue (BUN), fósforo (P), cálcio (Ca) total e ionizado, paratormônio (PTH) e fosfatase alcalina (ALP)]. A densidade mineral óssea foi mensurada na região da coluna lombar (L2-L4) no grupo de pacientes usando a absorciometria por raio-X de dupla energia (DXA). Resultados: Os níveis de cálcio total e ionizado eram significativamente menores, ao passo que o fósforo sérico, a FA e o PTH eram maiores em casos de SNSE e SNRE que nos controles. A osteopenia foi documentada pelo exame DXA em 11 pacientes (44%) e a osteoporose, em dois pacientes (8%). O risco de fratura era leve em seis (24%), moderado em dois (8%) e acentuado em três (12%) dos pacientes. Conclusão: A mineralização dos ossos foi afetada negativamente pelo tratamento com esteroides em crianças com SN. Keywords: Nephrotic syndrome, Bone mineral density, DXA scan, Palavras-chave: Síndrome nefrótica, Densidade mineral óssea, Exame DXA